TEMPORAL AND REGIONAL EVALUATION OF CHILDREN NUTRITIONAL STATUS IN THE STATE OF PARAÍBA - dos Santos Silva , Ana Rafaele; Caldas Amorim , Bianca; Xavier Cavalcanti , Laís Yasmin; Anderson,; Dantas, Renato Lima (Revista de Ciências da Saúde Nova Esperança, 2024)
Healthy eating is essential for quality of life and longevity, as it helps prevent diseases and supports the body's recovery. In the state of Paraíba, as in other regions of the Brazilian Northeast, childhood malnutrition, particularly among children aged 0 to 5 years, is rooted in issues such as poverty and limited access to healthcare services. To monitor the nutritional situation, the Food and Nutrition Surveillance System (SISVAN) collects data on children's food intake and nutritional status. This retrospective study aimed to compare the nutritional status of children in Paraíba from 2013 to 2023 using data from SISVAN. The analysis considered children's Body Mass Index (BMI), grouping the data into categories such as Severe thinness, Thinness, Eutrophy, At risk of overweight, Overweight, and Obesity. The results showed that eutrophy predominated, peaking in 2023 when about 99,515 children were at an ideal weight. However, the at risk of overweight and overweight indices increased, especially in the last three years, reaching 33,832 and 11,971 children in 2023, respectively. Obesity, although it showed some variations, remained relatively stable over the years. Underweight and severe underweight also showed minimal fluctuations. Despite the increase in children at risk of overweight, the growth rate was slower compared to the rise in eutrophic children. These findings highlight the importance of promoting healthy eating and public health policies to prevent malnutrition and the long-term consequences of an inadequate diet, which can lead to health problems. In 2023, 58.31% of children were eutrophic, while 41.69% had some nutritional deficit.